Transoral excision of parapharyngeal ganglioneuroma - Malak Almalki; Alanoud Hakami; Abdullah Arafat; Abdullah Albdah; Jaber Alshammri (Elsevier, 2020)
Parapharyngeal space tumors are rare, where they represent only 0.5% of all head and neck tumors. This paper describes a rare case of a ganglioneuroma isolated in the paraphayngeal space. A 7 years old female presented to the ENT outpatient clinic with sleep disturbance, snoring, mouth breathing and dysphagia. Physical examination revealed a bulging mass in the posterior pharyngeal wall indicating a congenital laryngeal mass. On imaging, Gadolinium-enhanced multi-sequential multi-planer MRI of the neck demonstrated well-defined large mass. The patient underwent surgical excision of the mass trans-orally and postoperative histopathological examination of the mass confirmed the final diagnosis as ganglioneuroma with Schwannoma stroma dominant. Post-operatively, the patient was in a good condition with no complications has been observed to date. To conclude, ganglioneuroma should be considered in the differential diagnosis of parapharyngeal space masses in pediatric, regardless of the presentation.